Abundance-Occupancy Relationships Along Taxonomic Ranks Reveal a Consistency of Niche Differentiation in Marine Bacterioplankton With Distinct Lifestyles - Izabel-Shen, Dandan; Höger, Anna-Lena; Jürgens, Klaus (Frontiers in Microbiology, 2021)
Abundance-occupancy relationships (AORs) are an important determinant of biotic community dynamics and habitat suitability. However, little is known about their role in complex bacterial communities, either within a phylogenetic framework or as a function of niche breadth. Based on data obtained in a field study in the St. Lawrence Estuary, we used 16S rRNA gene sequencing to examine the vertical patterns, strength, and character of AORs for particle-attached and free-living bacterial assemblages. Free-living communities were phylogenetically more diverse than particle-attached communities. The dominant taxa were consistent in terms of their presence/absence but population abundances differed in surface water vs. the cold intermediate layer. Significant, positive AORs characterized all of the surveyed communities across all taxonomic ranks of bacteria, thus demonstrating an ecologically conserved trend for both free-living and particle-attached bacteria. The strength of the AORs was low at the species level but higher at the genus and phylum levels. These results demonstrate that an assessment of the distributions and population densities of finely resolved taxa does not necessarily improve determinations of apparent niche differences in marine bacterioplankton communities at regional scales compared with the information inferred from a broad taxonomic classification.